Service, Satisfaction and Climate : Perspectives on Management in English Language Teaching. - Walker, John, 1947 March- (Innovation and Leadership in English Language Teaching, 2., 2010)
This book seeks to fill the gap through discussion of ELT as a service, issues surrounding ELT teachers as service providers, the work of ELT managers, client expectations and perceptions of ELT service, comparison of staff estimates and client ratings of service quality, and considerations of service milieu and climate in ELT centers.